CASE REPORT: CONCURRENT ASPERGILLOSIS, STAPHYLOCOCCOSIS AND COCCIDIOSIS IN BROILER CHICKENS IN BENOA, BALI - Putri, Dilyanti Maya; Widyasanti, Ni Wayan Helpina; Winaya, Ida Bagus Oka; Putra, I Putu Cahyadi; Astawa, I Nyoman Mantik (Buletin Veteriner Udayana, 2026)
Co-infection of Aspergillus fumigatus with Staphylococcus sp and Eimeria spp that occur in poultry farming systems has the potential to increase the severity of the disease and cause significant economic losses. This case report aims to report the results of a diagnosis of coinfection of the disease in broiler chickens at one of the farms in Benoa, South Kuta District, Badung Regency, Bali. The farm has a capacity of 16,000 heads with a closed cage system. The examination was carried out based on epidemiological fingerprints, anamnesis, clinical examination, pathology, bacteriological tests, mycology and parasitology. Clinical symptoms observed include anorexia, weakness, curled up, drowsiness, and being smaller than peers of his age (dwarf). Interview data showed that as many as 0.78% of the chicken population showed symptoms of disease (morbidity), with a mortality rate of 0.075%. About 1.05% of infected chickens die (CFR). The results of an anatomical pathology examination found a multisystemic form of aspergillosis characterized by many yellowish-white granulomas of various sizes in various organs, including the lungs, heart, proventriculus, ventricles, kidneys, spleen, and small intestine. On histopathological examination, there are special granulomatous lesions in which there are septated hyphae. Mycological tests showed the presence of Aspergillus fumigatus infection. Bacteriological tests identified the presence of Staphylococcus sp., while parasitological tests detected the presence of Eimeria spp. with a value of 12,300 oocysts per gram. Based on a series of examinations carried out, the case chickens experienced aspergillosis, staphycococosis, and coccidiosis at the same time. Coinfection of the disease needs to be a concern because it can make it difficult to diagnose and control the disease.